Student Interest in the Use of M-Banking in Single Tuition Payment - Mia Safirah; Annio Indah Lestari Nasution (Quantitative Economics and Management Studies, 2023)
This study was performed to assess student interest in using M-Banking to pay Single Tuition Fees. This research used a hybrid methodology, which combines qualitative and quantitative approaches. Sequential Exploratory Design is the sort of combination study performed, which employs qualitative approaches in the early stages of research and quantitative methods in the later stages. Quantitative approaches with an average score will be implemented. The average score of the indicators of student interest in M-Banking users in the payment of Single Tuition is 99.73%, according to the findings and conclusions of this study. This indicates that student interest in M-Banking is extremely high, particularly among FEBI UINSU students. The average score for the indicator of entrepreneurial interest is 99.96%. This indicates that the category falls within the high range, indicating that the average indicators of M-Banking users among FEBI UINSU students fall within the high range. The study also found that students use M-Banking since they can do transactions from home at any time. The average student can use an M-Banking app to pay tuition. This implies that student interest in M-Banking for single tuition costs is quite influential.